Pengaruh Bukti Fisik, Jaminan dan Penanganan Keluhan Terhadap Kepuasan Pasien BPJS (Studi Kasus pada RS Medika Dramaga Bogor) - Amalia Kautsar; Iis Anisa Yulia; Dewi Fitrianti; Mulyana Gustira Putra (Jurnal EMT KITA, 2023)
This research aims to determine the effect of Tangible Assets, Assurance and Complain Handling on BPJS Patient Satisfaction. The sample used in this study were 332 BPJS patient respondents at Medika Dramaga Hospital, Bogor. The analytical method used is multiple linear regression with the dependent variable is the patient satisfaction and as the independent variable is tangible assets, assurance and complaint handling. The results showed that tangible assets, assurance, and complaint handling had a significant effect on patient satisfaction, either partially or simultaneously. Of the three independent variables, the assurance variable has the most dominant effect on patient satisfaction.